Design of a gyroscopically stabilized single-wheeled robot - Saleh, Tanveer (2004)
Conventional design of mobile robot ensures its stability by keeping the gravity vector through the center of mass inside the structure's polygon of support determined by the contact points between the structure and the ground. This assumption of quasi-static stability fails to hold when the robots moves at high speed as the inertial forces become significant compared to the static gravitational force. On the otber hand, the momentum of the moving structure can be exploited to enhance stability if it is dynamically controlled. This principle was used exploited to build a gyroscopically stabilized single-wheeled robot by the researchers at Carnegie Melon University (CMU). Our design follows the same principle for stability but uses a different mechanism to effectuate the forward and reverse motion.